Large-scale land acquisitions: Focus on South-East Asia - Christophe Gironde; Christophe Golay; Peter Messerli (Brill Nijhoff, 2016)
This book examines large-scale land acquisitions, or `land grabbing', with a focus on South-East Asia. Thematic papers and detailed case studies put this phenomenon into specific historical and institutional contexts, analysing transformations in livelihoods, human rights impacts, and potential remedies.
Keywords: 320; Landnutzung; Bodenrecht; Soziale Lage; Menschenrechte; Entwicklung; Südostasien